Analisis Peran Kepemimpinan Walikota Terhadap Kesejahteraan Masyarakat di Kota Bekasi - Defalia Widamutia; Budi Supriyatno; Azis Hakim (CV. ULIL ALBAB CORP, 2025)
Bekasi City, as one of the largest metropolitan cities in Indonesia, exhibits high dynamics and complexity across various aspects, including community welfare. The Mayor of Bekasi holds the mandate to lead and manage the city’s administration, formulate policies and development programs, and ensure the achievement of development goals, including the improvement of community welfare. This article focuses on analyzing the role of the Mayor of Bekasi in fostering community welfare in the city. The research employs a qualitative method with descriptive analysis to examine the influence of leadership on community welfare in Bekasi. The findings indicate that the level of community welfare in Bekasi City has shown significant improvement over the past 10 years (2014–2024).